Production and profitability of diversified agricultural systems - VOLSI,BRUNO (2021)
Abstract Diversified crop rotation is an option for expanding producer incomes, and its adoption has presented a series of agronomic advantages compared to less diversified crop rotation systems. In this context, the objective of this study was to verify if higher-diversified crop rotation systems perform economically better than low-diversified ones. To this end, we conducted an experiment in no-tillage crop areas in Londrina, in south of Brazil, for the years 2014/15 to 2016/17. The experiment design was randomized blocks, with six treatments, consisting of crop rotation systems with different levels of diversification, and four replications. We observed that higher-diversified crop rotation systems yield higher revenues and profits. Only these systems, specifically the ones that included canola-corn, crambe-corn, and safflower-soybeans, or wheat-corn+brachiaria, canola-corn, and edible beans-soybeans were economically feasible. Despite higher cost, diversified systems with a greater number of commercial crops in winter presented higher profits. However, diversified systems with a high proportion of cover crops in winter are economically infeasible because their net return is negative.